Apprenticeship, vocational training, and early labor market outcomes – evidence from East and West Germany. Issue 1 (2nd January 2016) - Riphahn, Regina T.; Zibrowius, Michael
Abstract : We study the returns to apprenticeship and vocational training for three early labor market outcomes all measured at age 25 for East and West German youths: non-employment (i.e. unemployment or out of the labor force), permanent fulltime employment, and wages. We find strong positive effects of apprenticeship and vocational training. There are no significant differences for different types of vocational training, minor differences between East and West Germany and males and females, and no significant changes in the returns over time. Instrumental variable estimations confirm the regression results. The positive returns hold up even in poor labor market situations.